Legal Sociology Review of The Development of Land Services in Indonesia - Waldani, Izmi (JLAST : Journal of Law and Social Transformation, 2024)
Abstract This study investigates the complex relationship between Indonesian social dynamics and the legal framework governing land development, examining the implications for societal welfare and legal certainty. Indonesia's land governance environment is changing dramatically as a result of fast population expansion and the shift to the digital era. Despite the desire for an equitable and flourishing society, gaps exist between the idealistic goals of community development and the practical implementation of agrarian legislation. This study seeks to answer the following questions: the impact of Indonesian social behavior on law creation and implementation, the impact of social structures on legal interpretation, the role of community organizations and governmental bodies in legal regulation, and the evolution of land service through the lens of legal sociology. By examining these issues, this study hopes to provide insights into the complexity of land development in Indonesia, with an emphasis on increasing legal clarity and promoting societal well-being.